2012
DOI: 10.1159/000339417
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Exhalation of Matrix Metalloproteinase-9 and Tissue Inhibitor of Metalloproteinase-1 in Patients with COPD Exacerbation: A Prospective Study

Abstract: Background: Matrix metalloproteinase-9 (MMP-9) and its inhibitor tissue inhibitor of metalloproteinase-1 (TIMP-1) are involved in the pathogenesis of airway inflammation in patients with chronic obstructive pulmonary disease (COPD). However, no study so far has addressed their value as noninvasive biomarkers of airways inflammation. Objective: To evaluate MMP-9 and TIMP-1 concentrations in the exhaled breath condensate (EBC) of patients with stable COPD and also during the exacerbation episode. Methods: EBC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 53 publications
2
23
0
2
Order By: Relevance
“…On the other hand, MMP-9 is inhibited by TIMP-1 and an imbalance in the MMP-9/TIMP-1 ratio could be involved in COPD pathogenesis. In this regard, Kang et al demonstrated a correlation among the increase in the MMP-9/TIMP-1 complex in lung tissue from smokers and the airflow obstruction observed [31] and Higashimoto et colleagues [20] found that circulating TIMP-1 concentration was significantly higher in stable COPD patients. This and our report suggest that excess amounts of TIMP-1 compared with those of MMP-9 may be related to airway narrowing.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MMP-9 is inhibited by TIMP-1 and an imbalance in the MMP-9/TIMP-1 ratio could be involved in COPD pathogenesis. In this regard, Kang et al demonstrated a correlation among the increase in the MMP-9/TIMP-1 complex in lung tissue from smokers and the airflow obstruction observed [31] and Higashimoto et colleagues [20] found that circulating TIMP-1 concentration was significantly higher in stable COPD patients. This and our report suggest that excess amounts of TIMP-1 compared with those of MMP-9 may be related to airway narrowing.…”
Section: Discussionmentioning
confidence: 99%
“…The SLPI level is higher and is negatively correlated with FEV/FVC in patients with COPD (53). A prospective study proposed that the expression of TIMP-1 in exhaled breath condensate is higher in patients with stable COPD (54). The increased TIMP-1 expression is closely related with COPD exacerbation (54).…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study proposed that the expression of TIMP-1 in exhaled breath condensate is higher in patients with stable COPD (54). The increased TIMP-1 expression is closely related with COPD exacerbation (54). In the present study, it was demonstrated that the levels of inflammation-related factors, including SP-D, PCT, sTREM-1, SAA, IP-10 and TRAIL, as well as protease molecules such as NE, α1-AT, SLPI and TIMP-1, were significantly ameliorated in the intervention group compared with the control group at 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Матриксна металопро-теїназа-9 (ММП) грає важливу роль беручи участь в процесі патогенезу серцево-судинних захворю-вань, так само має достовірний кореляційний зв'язок з рівнем бронхіальної обструкції. У дослідженні Hurst R. et al була доведена висока чутливість та специфічність такого маркера запалення як вч-СРБ серед 36 біомаркерів, однак кращою комбінацією в порівнянні з одним цим маркером було визначення додатково тріади біомаркерів ММП-9, вч-СРБ, фак-тор інгібування мієлоїдних попередників [12,14,15]. Отримані результати досліджень демонструють ви-соку специфічність і чутливість маркерів запалення ММП-9 і вч-СРБ, проте враховуючи малу кількість досліджень при поєднанні ГХ та ХОЗЛ, потрібне подальше вивчення даної патології.…”
Section: обґрунтування дослідженняunclassified